What could be the function of the spinal muscular atrophy-causing protein SMN in macrophages? - Tapken, Ines; Detering, Nora T.; Claus, Peter (Frontiers in Immunology, 2024)
Spinal Muscular Atrophy (SMA), a neurodegenerative disorder, extends its impact beyond the nervous system. The central protein implicated in SMA, Survival Motor Neuron (SMN) protein, is ubiquitously expressed and functions in fundamental processes such as alternative splicing, translation, cytoskeletal dynamics and signaling. These processes are relevant for all cellular systems, including cells of the immune system such as macrophages. Macrophages are capable of modulating their splicing, cytoskeleton and expression profile in order to fulfil their role in tissue homeostasis and defense. However, less is known about impairment or dysfunction of macrophages lacking SMN and the subsequent impact on the immune system of SMA patients. We aimed to review the potential overlaps between SMN functions and macrophage mechanisms highlighting the need for future research, as well as the current state of research addressing the role of macrophages in SMA.